Self Disclosure dalam Komunikasi Diadik antara Mahasiswa dan Dosen Penasehat Akademik - Aminah Swarnawati (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2021)
The study of self disclosure in educated communication between students and academic advisory lecturers focuses the problem on non-academic issues that affect students' academic achievement. The purpose of the research is 1) to analyze student self-disclosure to academic advisory lecturers based on the dimensions of self disclosure; 2) analyze student self disclosure to PA lecturers based on factors that influence self-disclosure. The research method uses a qualitative approach with a descriptive analysis technique. The results revealed the dimensions of self disclosure: dimension size/frequency, frequency of frequent consultation, consultation time is not long; The valence tends to be negative; dimensions of carefulness and honesty still need more in-depth observation; there is a familiarity that is intertwined. Meanwhile, based on the influencing factors, that is, there is no dyadic effect; the size of a two-person audience; topics from academic problems develop to non-academic issues. The valence factors are favorable to negative; religion, ethnicity, community, gender, and age: relatively the same; partner factors between student-PA positions are not equal. Keyword: dyadic communication, interpersonal communication, self-disclosure